A HEALTH EDUCATION ON THE IMPACT OF SMOKING ON THE INCIDENCE OF LUNG CANCER IN THE COMMUNITY GROUP OF BLOK I CITRA LAND MAS HOUSING, KUBANG JAYA VILLAGE - Widiyanto, Juli; Kusumaningrum, Tri Siwi; Maaswarni, Maswarni; Gasril, Pratiwi (LP2M STP Mataram, 2024)
Background : Lung cancer is a malignant tumor that arises from outside the lungs or from within the lungs themselves, where abnormalities can be caused by genetic changes in the epithelial cells of the respiratory tract that can cause uncontrolled cell proliferation. The majority of lung cancers can be triggered by a history of smoking. both active smokers and passive smokers. Partners in this PKM activity are community groups in Block I of Citra Land Mas Housing, Kubang Jaya Village, Kampar. Most of the men in the Block I area are active smokers. This Community Service Activity aims to increase public knowledge of the impact of smoking on the incidence of lung cancer. Methods : This community service method uses lectures and discussions about the impact of smoking on the incidence of lung cancer which includes types of cigarettes, cigarette content, the effects of cigarette content on the human body, Result : The results of Community Service activities show that public knowledge after being given education increased by the majority in the good category of 75% compared to before being given health education about the impact of smoking on the incidence of lung cancer